Structure factor of the gas sensitivity improvement of bilayer tin dioxide films - Panchekha, P.A.; Novikov, V.A. (Functional Materials, 2005)
Comparative studies of electric conductivity and gas sensitivity have been carried out for two types of tin dioxide films (single- and bilayer ones). The free surface area of the bilayer films was increased intentionally by applying the second layer as a thin nanodis-persed tin dioxide layer with a developed relief. The gas sensitivity of the bilayer films has been shown to exceed by 2 to 4 times that of the single-layer ones at the same thickness. This and others features of the bilayer films have been explained by the improved adsorbing ability thereof and, consequently, by a stronger depletion of free charge carriers in the layer at oxygen adsorption.